2020
DOI: 10.1111/ijcp.13489
|View full text |Cite
|
Sign up to set email alerts
|

Non‐prescription medicines may contribute to non‐adherence to prescription medicines in people living with chronic health conditions

Abstract: Background Non‐adherence to prescribed medicines is linked to adverse health outcomes in people living with chronic health conditions (CHCs). Multiple factors are known to contribute to non‐adherence to medicines including polypharmacy, demographic features and disease and health systems. Both non‐prescription and prescription medicines contribute to polypharmacy; however, there is limited data on the influence of non‐prescription medicines to non‐adherence. Aim Therefore, the aim of the study was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…health literacy), drug-related factors (e.g. adverse effects), the patient-provider relationship, difficulties of obtaining medications, and the use of non-prescription medications [ 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…health literacy), drug-related factors (e.g. adverse effects), the patient-provider relationship, difficulties of obtaining medications, and the use of non-prescription medications [ 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with 0-1 comorbidity had higher medication adherence than patients with 2 or more comorbidities (p = 0.019). The results of previous studies also showed that people having multiple comorbidities and using multiple drugs at the same time often had a lower medication adherence [26,27]. This could be because patients with multiple comorbidities tend to use many drugs, making it challenging for them to manage their conditions and more likely to forget to use their medications more often.…”
Section: Discussionmentioning
confidence: 98%
“…Participants also reported using OTC treatments. While concurrent use of non‐prescription medications is reported as a barrier to adherence (Anoopkumar‐Dukie et al., 2020), there is a tendency among patients to withhold details of OTC drug use from their GP (Moen, Norrgård, Antonov, Nilsson, & Ring, 2010). Our results therefore highlight that the burden of medications is not restricted to long‐term prescribed treatments, and other medicines may contribute to challenges with adherence.…”
Section: Discussionmentioning
confidence: 99%